IMPROVING STUDENT PRONUNCIATION SKILLS THROUGH PHONETIC SYMBOLS - Hermansyah, Sam; Kaur, Parwinder; Monteza, Ana Mae M.; Dennison.J, Evans; Mohamed S.H, Sheik (La Ogi : English Language Journal, 2025)
This study aimed to explore the effectiveness of phonetic symbols in enhancing the pronunciation skills of second-semester students in the English Department at the University of Muhammadiyah Sidenreng Rappang. The research utilized a quasi-experimental design involving two groups: an experimental group that was taught using phonetic symbols and a control group that followed conventional pronunciation methods. Both groups underwent pre-tests and post-tests to evaluate their pronunciation abilities. Results were analyzed using t-tests with the aid of SPSS software. The findings revealed a significant improvement in the pronunciation skills of the experimental group, with the post-test scores showing a substantial increase compared to the control group. Additionally, the students expressed a strong interest in using phonetic symbols for pronunciation practice, as indicated by their responses to a questionnaire. This study concludes that teaching pronunciation through phonetic symbols effectively enhances students' pronunciation abilities and is well-received by learners.